Cooking up creative solutions.(creative thought among research scientists) - Wiley, Steven H (The Scientist, 2012)
Most scientists have a hard enough time keeping up with new work in their own subject, much less trying to understand what other scientists are doing. Because I work in a large, multidisciplinary research institute, I am constantly exposed to a great many different areas of science, albeit in a mostly superficial fashion. [...]we usually are left with a general correlation between a pathway and a response.